Syntaxonomical update on the relict groves of Scots pine (Pinus sylvestris var. iberica) and Spanish black pine (Pinus nigra subsp. salzmannii) in the Gredos range (central Spain) - López Sáez, José Antonio; Sánchez-Mata, Daniel; Gavilán, Rosario G. (Lazaroa, 2016)
Pure and mixed high-mountain pine forest vegetation of the Gredos range (central Spain) was studied using 57 relevés and multivariate analyses (hierarchical cluster analysis and detrended correspondence analysis). Classification of the relevés resulted in 7 vegetation units, 3 of which were ranked as associations and only one as subassociation. DCA diagrams of relevés and taxa indicated that floristic differentiation was attributed mainly to factors such as altitude. Differential taxa of vegetation units were chosen based on their phi coefficient values. The statistic discrimination of some of these vegetation units has allowed us to propose a new association and a new subassociation of other community described in a previous paper.